The Influence of Nicotinamide on Health and Disease in the Central Nervous System. (21st May 2018) - Fricker, Rosemary A; Green, Emma L; Jenkins, Stuart I; Griffin, Síle M
Nicotinamide, the amide form of vitamin B3 (niacin), has long been associated with neuronal development, survival, and function in the central nervous system (CNS), being implicated in both neuronal death and neuroprotection. Here, we summarise a body of research investigating the role of nicotinamide in neuronal health within the CNS, with a focus on studies that have shown a neuroprotective effect. Nicotinamide appears to play a role in protecting neurons from traumatic injury, ischaemia, and stroke, as well as being implicated in 3 key neurodegenerative conditions: Alzheimer's, Parkinson's, and Huntington's diseases. A key factor is the bioavailability of nicotinamide, with low concentrations leading to neurological deficits and dementia and high levels potentially causing neurotoxicity. Finally, nicotinamide's potential mechanisms of action are discussed, including the general maintenance of cellular energy levels and the more specific inhibition of molecules such as the nicotinamide adenine dinucleotide-dependent deacetylase, sirtuin 1 (SIRT1).